The practice of leisure reading : the effects on mental well-being and sleep quality in university students - Ísabella D Sigursteinsdóttir 2001- (2024)
The purpose of this study is to examine the effects of leisure reading on mental well-being and sleep quality in students in Iceland. Research suggests there is a relation between leisure reading and lower odds of depression. Leisure reading can be a coping mechanism in difficult life circumstances and has been proven to increase sleep quality. The aim of this study is to see whether leisure reading could affect students’ mental well-being. Furthermore, to see if leisure reading could affect sleep quality, and if that could explain changes in mental well-being. Mental well-being, sleep quality and leisure reading is the focuses for this study. The “Warwick-Edinburgh Mental Wellbeing scale” is chosen for the mental well-being questions and the “Pittsburg Sleep Quality Index” is chosen for the sleep quality questions. There were 458 participants. The study shows a positive correlation between leisure reading and mental well-being, with sleep quality as a mediator, though it was insignificant. In conclusion, based on the Pearson’s correlation, there is insignificant correlation between leisure reading and the two variables, mental well-being and sleep quality. This study does not affirm the hypothesis and can thus be used as a starting point for future research on this matter. Keywords: Leisure reading, Mental Well-Being, Sleep Quality, University students Tilgangur þessarar rannsóknar er að skoða áhrif yndislesturs á andlega heilsu og svefngæði nemenda við Háskólann í Reykjavík. Rannsóknin gefur til kynna að það sé samband milli yndislesturs og líkum á þunglyndi. Yndislestur getur nýst sem bjargráð eftir erfiða lífsreynslu og hefur verið sýnt fram á að hann stuðli að betri svefngæðum. Markmið þessarar rannsóknar var að sjá hvort yndislestur gæti haft áhrif á andlega heilsu. Einnig var markmiðið að sjá hvort áhrif yndislesturs á svefngæði, gæti útskýrt breytingu á andlegri heilsu. Í spurningalistanum var meðal annars spurt út í yndislestur, andlega heilsu og svefngæði. Fyrir spurningar um andlega heilsu var notað ...